The gruffalo - Donaldson, Julia; Scheffler, Axel (New York : Dial Books for Young Readers, 1999)
A clever mouse uses the threat of a terrifying creature to keep from being eaten by a fox, an owl, and a snake-- only to have to outwit that creature as well.
School Library Journal, August 1999
Publisher's Weekly, June 1999
Booklist, July 1999
School Library Journal
Publisher's Weekly
Booklist
Keywords: Mice -- Fiction; Animals -- Fiction; Stories in rhyme; Mice -- Fiction; Animals -- Fiction; Stories in rhyme